Signature of magmatic processes in strainmeter records at Campi Flegrei (Italy). Issue 2 (21st January 2017) - Bagagli, M.; Montagna, C.P.; Papale, P.; Longo, A.
Abstract: Volcanic unrest at Campi Flegrei caldera, Southern Italy, is characterized by episodes of ground deformation, seismicity, and enhanced fumarolic activity; whether its origin is purely hydrothermal or magmatic is highly debated. We have identified ground deformation patterns in strainmeter records from a heightened unrest period in late 2006, closely resembling synthetic signals from numerical simulations of shallow magma chamber replenishment and mixing. Together with other recent findings, our results depict a situation whereby periodic arrivals of deep magma feed a shallow intrusion at 3–4 km depth. These results suggest that the analysis of strainmeter records, coupled with advanced numerical simulations of magma dynamics, could lead to new approaches in imaging subsurface dynamic processes in volcanic areas. Key Points: Comparison between strain records and synthetic ground deformation caused by magma mixing Identification of transients where similarity is large indicating magma movement Detection of magma dynamics from analyses of ground deformation signals at active volcanoes